Role of stem cells in the treatment of osteoarthritis- a review of literature - Mohammad Mustafa; Arslan Ahmed Abro; Noman Khan; Muhammmad Kazim Rahim Najjad; Syed Shahid Noor (Journal of the Pakistan Medical Association, 2023)
The purpose of this review was to identify and assess the effectiveness of stem cells in the form of injectables in the treatment of joint osteoarthritis as published in the literature. Studies were searched from multiple databases like Pubmed, Embase and Cochrane Library until June 2022 using multiple keywords. Randomized controlled trials of patients with osteoarthritis (OA) were included which compared the pain and functional outcomes for those getting Mesenchymal Stem Cells (MSCs) injectables as compared to those who received no MSCs injection. Twelve randomized controlled trials, assessing a total of 486 participants were identified and studied. Overall, stem cells injection has no significant effect on pain along with physical function. Continued